Kepemimpinan Transformasional, Stress Kerja dan Kinerja Karyawan - Fardillah, Izmi (Persona:Jurnal Psikologi Indonesia, 2016)
This research aim to know the relation between transformational leadership and workstress with work performance. To know that relation got obtained from 63 responder employee.Got data to be analyzed with double regression and correlation analyzed of parsial. The result ofanalysed got double regression F = 698.796 with p = 0,000 (p < 0,01) it’s mean there aresignificant relation between transformational leadership and work stress with work performance.Learn this finding indicate that hypothesis expressing said that there is relation betweentransformational leadership and work stress with work performance earn provenly was accepted.Result of parsial analisist show relation between work stress with transformational leadershipobtainedt = 0,137 dengan p = 0,892 (p > 0,05) that’s mean no relation between transformationalleadership with work performance. The relation between work motivation and work performanceobtained t = 6.067 dengan p = 0,000 (p < 0,01) that’s mean positive relation which verysignificant between work stress with work performance. As higher work stress so that as lowerwork performance.Keywords : transformational leadership, work stress, work performance